How the brain learns - Sousa, David A. (Corwin, 2011)
Latest edition includes updated information on brain processes including memory systems; how the explosion of technology affects the brain; and how learning and participating in the arts enhances cognitive processing and creativity. Includes more than 150 new references and an expanded index